2016
DOI: 10.1073/pnas.1515828113
|View full text |Cite
|
Sign up to set email alerts
|

Clocking the social mind by identifying mental processes in the IAT with electrical neuroimaging

Abstract: Why do people take longer to associate the word "love" with outgroup words (incongruent condition) than with ingroup words (congruent condition)? Despite the widespread use of the implicit association test (IAT), it has remained unclear whether this IAT effect is due to additional mental processes in the incongruent condition, or due to longer duration of the same processes. Here, we addressed this previously insoluble issue by assessing the spatiotemporal evolution of brain electrical activity in 83 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 79 publications
7
40
0
Order By: Relevance
“…Neural correlates of the IAT (see e.g. Schiller et al, 2016) are of high interest as they would offer a more direct insight into the interaction of neurological and social aspects of. and 'i' for negative concepts in block one and similarly in block one with the keys 'e' for complete bodies and 'i' for amputated bodies.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Neural correlates of the IAT (see e.g. Schiller et al, 2016) are of high interest as they would offer a more direct insight into the interaction of neurological and social aspects of. and 'i' for negative concepts in block one and similarly in block one with the keys 'e' for complete bodies and 'i' for amputated bodies.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Only one study examined event-related potentials (ERPs) of an addiction-related IAT in a sample of patients with Internet addiction (Chen et al, 2018). Along with reports on early components (e.g., P1;Fleischhauer et al, 2014), those studies have repeatedly indicated that the amplitude (Chen et al, 2018;Coates and Campbell, 2010;Xiao et al, 2015) and timing (Schiller et al, 2016) of the N2 component differ between incongruent and congruent trials, which was attributed to a larger preresponse conflict in incongruent trials.…”
mentioning
confidence: 99%
“…Respondents are required to make a quick response within a time limit of less than a second in order to avoid allowing time for rational thought. The idea behind the test is that a congruent pairing of an attribute and ‘Yes’ or ‘No’ will elicit a faster response than an incongruent pairing [7] .…”
Section: Format For Semantic Priming Testsmentioning
confidence: 99%